Efficacy of Simple Eye Ointment, Polyethylene Cover, and Eyelid Taping in Prevention of Ocular Surface Disorders in Critically Ill Patients: A Randomized Clinical Trial - Mehdi Ahmadinejad; Esmat Karbasi; Yunes Jahani; Maryam Ahmadipour; Maryam Soltaninejad; Zahra Karzari (Critical Care Research and Practice)
Background. Under normal conditions, the cornea of the eye is protected from bacterial invasion, physical injury, and drying by the presence of tears, eyelids, and blinking reflex. However, patients admitted to the intensive care unit (ICU) for several reasons including loss of consciousness, receiving sedative and neuromuscular blocking agents, and mechanical ventilation may lose eye-protective mechanisms causing exposure keratopathy. Therefore, this study intended to compare three eye care methods to prevent ocular surface disorders (OSDs) in ICU patients. Methods. This study was a double-blind clinical trial (IRCT: 201109225426N3, https://www.irct.ir/trial/5825), in which 152 patients were randomized into three groups and each group underwent a different eye care procedure. The eye care methods included simple eye ointment, polyethylene cover, and eyelid taping. The eligible patients received the care procedure for seven days, and their corneas were examined daily for OSD by a portable slit lamp with fluorescein staining. Descriptive and analytical tests (ANOVA, chi-square, logistic regression, and zero-inflated Poisson regression) were used for statistical analysis by STATA14. Results. The odds of OSD (chances of getting an OSD grade between I and VI) in the ointment group were 0.19 (95% CI: 0.09, 0.41), and the odds of OSD in the polyethylene cover group were 0.06 (95% CI: 0.01, 0.20), showing a significant difference with the tape group (p=0.0001). Despite the lower odds of OSD in the cover group than in the ointment group, there was no significant between-group difference (p=0.08). However, the mean OSD scores in both the ointment and polyethylene cover groups were significantly lower than that in the tape group. Conclusion. The results of this study showed that polyethylene cover followed by simple eye ointment and eyelid taping were the most effective methods in preventing OSD. Therefore, polyethylene cover and simple eye ointment are recommended as effective eye care methods in ICU.